KAJIAN EKSISTENSI PRODUK GARAM DARAT DI DESA JONO, KECAMATAN TAWANGHARJO, KABUPATEN GROBOGAN, JAWA TENGAH - Wafi Yoga Pratama; Ali Zainal Abidin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Jono Village, Tawangharjo District, Grobogan Regency is one of the ground salt producing areas. Jono salt is a salt product that is unique and has a distinctive taste. This study uses a qualitative approach with case study analysis, aims to determine the existence of a unique product, namely ground salt, and examines the condition of ground salt farmers in Jono Village, Tawangharjo District, Grobogan Regency, Central Java. This study used observation and interview methods with 12 informants. The results showed that Jono's Salt had a good existence in terms of taste, popularity, price and distribution. However, the quality of salt is below SNI. Jono's salt farmers feel that Jono's salt products are very promising and the area where they are produced has the potential to become a tourism village.